2020
DOI: 10.1186/s13059-020-01979-4
|View full text |Cite
|
Sign up to set email alerts
|

RADAR: annotation and prioritization of variants in the post-transcriptional regulome of RNA-binding proteins

Abstract: RNA-binding proteins (RBPs) play key roles in post-transcriptional regulation and disease. Their binding sites cover more of the genome than coding exons; nevertheless, most noncoding variant prioritization methods only focus on transcriptional regulation. Here, we integrate the portfolio of ENCODE-RBP experiments to develop RADAR, a variant-scoring framework. RADAR uses conservation, RNA structure, network centrality, and motifs to provide an overall impact score. Then, it further incorporates tissue-specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Lines of previous studies have demonstrated that truly functional CREs are highly conserved across both populations and species when compared to random genomic regions, as reflected by their depleted patterns in common variants and higher conservation scores in comparative genomics analysis ( 33 , 34 ). Therefore, we further compared the DIRECT-NET’s predicted HC CREs with the MC and LC regions using both cross-population and cross-species conservation.…”
Section: Resultsmentioning
confidence: 86%
“…Lines of previous studies have demonstrated that truly functional CREs are highly conserved across both populations and species when compared to random genomic regions, as reflected by their depleted patterns in common variants and higher conservation scores in comparative genomics analysis ( 33 , 34 ). Therefore, we further compared the DIRECT-NET’s predicted HC CREs with the MC and LC regions using both cross-population and cross-species conservation.…”
Section: Resultsmentioning
confidence: 86%
“…To determine the effect of these 3′-UTR piSNVs on RBP binding, we integrated RBP motif and CLIP-seq-derived RBP binding data 38 , 39 for all identified 3’-UTR piSNVs, which revealed 24 significantly enriched RBPs. Abnormal expression of RBPs leads to tumorigenesis 3 , so we detected the differentially expressed RBPs between tumor and corresponding normal tissues in different cancer types (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PIVAR algorithm was our previously developed to evaluate the impact of mutations on posttranscriptional regulation 6 . We updated PIVAR algorithm to evaluate the impact of mutations on posttranscriptional regulation by adding the latest 318 eCLIP-seq data from ENCODE (112 RBPs) to identify 3′-UTR piSNVs 38 , 39 , which could disrupt the binding between RNAs and RBPs. We used the Wilcoxon rank-sum test to compare the distribution of the 3′-UTR piSNV ratio (ratio of 3′-UTR piSNVs to 3′-UTR SNVs) between the control samples and samples of each cancer type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale identification and analysis of RBP targets will also aid in understanding the role of RBPs in disease. Recent advances in technology have made this possible [ 296 ]; however, these studies would be well complemented by follow up studies in tissues of interest.…”
Section: Discussionmentioning
confidence: 99%